Creating a typology of temporary landscapes - Fox, Rachel E. (Kansas State University, 2015)
Temporary landscapes are an emerging project type with in the field of landscape architecture. Pop-up parks, parklets, and temporary art installations have been gaining media attention and changing notions of open space. Landscape architects need to take a more active role in the planning, design, and execution of these temporary landscapes. Peter Bishop describes temporary land use as “an intentional phase” where the “time-limited nature of the use is generally explicit” (Bishop, 2012, p. 5). This research refines Bishop’s definition by stating temporary landscapes must be intentionally time limited designs of open space. Currently the unorganized variety of projects has impeded landscape architects’ ability to evaluate and learn from these spaces. This research project seeks to understand and synthesize different characteristics of temporary landscapes. A typology was developed by identifying key themes in literature, composing a carefully curated series of precedent studies, participating in the development of a temporary pop-up park in Wichita, Kansas, and developing a matrix that identifies the relationships between temporal types. The products of this research will help planners and designers develop more successful and intentional temporally limited designs.
Keywords: Landscape typology; Pop-up park; Temporary land useTemporary landscapes; Area Planning and Development (0341)